Sensitivity study of ice crystal optical properties in the 874 GHz submillimeter band. (July 2016) - Tang, Guanglin; Yang, Ping; Wu, Dong L.
Abstract: Testing of an 874 GHz submillimeter radiometer on meteorological satellites is being planned to improve ice water content retrievals. In this paper we study the optical properties of ice cloud particles in the 874 GHz band. The results show that the bulk scattering and absorption coefficients of an ensemble of ice cloud particles are sensitive to the particle shape and effective diameter, whereas the latter is also sensitive to temperature. The co-polar back scattering cross-section is not sensitive to particle shape, temperature, and the effective diameter in the range of 50–200 μm. Highlights: Optical properties of ice crystals at the 874 GHz band are studied. Both scattering and absorption are sensitive to particle shape and size. Absorption is also sensitive to temperature.